2019
DOI: 10.1038/s41598-019-44748-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics of Phytase-transgenic Maize Seeds Indicates Environmental Influence is More Important than that of Gene Insertion

Abstract: Proteomic differences were compared between phytase-transgenic (PT) maize seeds and nontransgenic (NT) maize seeds through two-dimensional electrophoresis (2-DE) with mass spectrometry (MS). When maize was grown under field conditions, 30 differentially accumulated proteins (DAPs) were successfully identified in PT seeds (PT/NT). Clusters of Orthologous Groups (COG) functional classification of these proteins showed that the largest group was associated with posttranslational modifications. To investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…These results are consistent with previously reported results for some other GM plants, such as transgenic maize, soybean and Arabidopsis 6, 30–33 . However, DAPs are not exclusively detected in GM crops but rather have also been observed during conventional plant breeding, 30, 34 hybridization 5, 24, 35 and even in different growth environments 36 …”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previously reported results for some other GM plants, such as transgenic maize, soybean and Arabidopsis 6, 30–33 . However, DAPs are not exclusively detected in GM crops but rather have also been observed during conventional plant breeding, 30, 34 hybridization 5, 24, 35 and even in different growth environments 36 …”
Section: Discussionsupporting
confidence: 93%
“…We believe that rice is a good model plant for those investigations, as it is an important food crop and has been widely used in the past for plant biology studies, including omics analyses. Previous studies have suggested that environmental stresses brought more biological variation than transgenesis and genetic background in plants (Ouakfaoui and Miki, 2005;Batista et al, 2008;Montero et al, 2011;Asiago et al, 2012;Batista et al, 2017;Wang et al, 2018b;Tan et al, 2019). In the present study, the seeds of all 13 rice lines were prepared in the same way and were cultivated and managed under the same conditions in a greenhouse to minimize the effects of varying environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The advancements in omics‐based systems biology including genomics, transcriptomics, proteomics and metabolomics profiling have greatly enhanced the possibilities to analyze unintended changes in plants and these techniques have been shown to be powerful approaches for identifying changes in GE plants, as has been demonstrated for example for Arabidopsis, rice, maize, soybean, barley and pigeon pea (Kuiper et al ., 2001; Ouakfaoui and Miki, 2005; Ricroch et al ., 2011; Gong and Wang, 2013; Herman and Price, 2013; Wang et al ., 2018b; Tan et al ., 2019). However, in most study cases comparative analyses were restricted to one GE line and its closest non‐GE counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…41 A review of publications comparing the proteomes of transgenic versus non-transgenic plants showed a range of results. In many studies, the differences were minor, [42][43][44][45][46][47][48][49][50] while in some others the changes were substantial. [51][52][53] However, in most of these researches, no toxic or allergenic proteins were identified.…”
Section: Discussionmentioning
confidence: 99%
“…56 Furthermore, numerous studies have shown that the effects caused by environmental factors or conditions on protein profile are greater than or similar to the effects of single gene insertion. [45][46][47]49,52,53 To know whether the observed changes in protein expression in transgenic sugar beet events compared to the wild type are less than alterations due to environmental factors such as biotic and abiotic stresses, studies on protein profiles of sugar beet under stress conditions was reviewed. For instance, protein extracts of sugar beet genotypes resistant and susceptible to Fusarium oxysporum were compared with control samples in two and five days postinoculation by Larson and her colleagues.…”
Section: Discussionmentioning
confidence: 99%